Unique N-glycosylation signatures in human iPSC derived microglia activated by Aβ oligomer and lipopolysaccharide - Xinyu Tang; Ryan Lee Schindler; Jacopo Di Lucente; Armin Oloumi; Jennyfer Tena; Danielle Harvey; Carlito B. Lebrilla; Angela M. Zivkovic; Lee-Way Jin; Izumi Maezawa (Scientific Reports)
Abstract Microglia are the immune cells in the central nervous system (CNS) and become pro-inflammatory/activated in Alzheimer’s disease (AD). Cell surface glycosylation plays an important role in immune cells; however, the N-glycosylation and glycosphingolipid (GSL) signatures of activated microglia are poorly understood. Here, we study comprehensively combined transcriptomic and glycomic profiles using human induced pluripotent stem cells-derived microglia (hiMG). Distinct changes in N-glycosylation patterns in amyloid-β oligomer (AβO) and LPS-treated hiMG were observed. In AβO-treated cells, the relative abundance of bisecting N-acetylglucosamine (GlcNAc) N-glycans decreased, corresponding with a downregulation of MGAT3. The sialylation of N-glycans increased in response to AβO, accompanied by an upregulation of genes involved in N-glycan sialylation (ST3GAL4 and 6). Unlike AβO-induced hiMG, LPS-induced hiMG exhibited a decreased abundance of complex-type N-glycans, aligned with downregulation of mannosidase genes (MAN1A1, MAN2A2, and MAN1C1) and upregulation of ER degradation related-mannosidases (EDEM1-3). Fucosylation increased in LPS-induced hiMG, aligned with upregulated fucosyltransferase 4 (FUT4) and downregulated alpha-L-fucosidase 1 (FUCA1) gene expression, while sialofucosylation decreased, aligned with upregulated neuraminidase 4 (NEU4). Inhibition of sialylation and fucosylation in AβO- and LPS-induced hiMG alleviated pro-inflammatory responses. However, the GSL profile did not exhibit significant changes in response to AβO or LPS activation, at least in the 24-hour stimulation timeframe. AβO- and LPS- specific glycosylation changes could contribute to impaired microglia function, highlighting glycosylation pathways as potential therapeutic targets for AD.